The Effectiveness of Health Promotion Using Leaflet Media and Poster Media on The Knowledge of Mother Todders About Stunting - Urhuhe Dena Siburian; Paruhum Tiruon Ritonga (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Stunting is a chronic nutritional problem in Indonesia. To reduce stunting rates, a strategy is needed, namely an advocacy approach with health promotion through education. This study aims to determine the effectiveness of leaflet and poster media in increasing knowledge about stunting. This type of research is quasi-experimental with pretest and posttest group design. This research was conducted at the Sitompul Village Posyandu and the Lumbansiagian Jae Village Posyandu in the Siatasbarita Health Center working area which was carried out from July to August 2023. The population was mothers of toddlers. The sample was mothers of toddlers who came to the posyandu in August and September 2023 in Sitompul Village and Lumbansiagian Jae totalling 30 people. The sampling technique was accidental sampling. The sample was given counselling using leaflet and poster media. Data analysis with univariate and bivariate analysis using Paired Sample T Test. The results showed that leaflet media was effective in increasing knowledge with a p-value = 0.000 (α < 0.05) and poster media was also effective in increasing knowledge with a p value = 0.001 (α < 0.05). However, there was no difference in the effectiveness of leaflet media and poster media in improving knowledge with a p-value = 0.464 (α > 0.05). The conclusion is that leaflets and poster media are effective in ienhancingknowledge. There is no difference in effectiveness between leaflet and poster media. It is expected that health workers will be more innovative in using educational media by combining media to be more effective in increasing knowledge Keywords: Effectiveness, Extension, Knowledge, Leaflets, Posters